Glycaemic Response to Acute Aerobic and Anaerobic Exercise Performed in the Morning or Afternoon in Healthy Subjects: A Crossover Trial - Alba Rodriguez-Muñoz; José Ignacio Martínez-Montoro; Belen Sojo-Rodriguez; Javier Benitez-Porres; Margarita Carrillo-Albornoz-Gil; Laura Carrasco-Fernandez; Alba Subiri-Verdugo; Ana Molina-Ramos; Andrés Cobos-Diaz; Francisco J. Tinahones; Almudena Ortega-Gomez; Mora Murri (Journal of the International Society of Sports Nutrition)
Background The regular practice of physical activity is considered a health promoter and appears to be one of the main contributors to the prevention of chronic diseases. However, the potential effects of exercise on health depending on the time of day at which it is performed have not yet been fully elucidated.Objectives To evaluate the effect of physical exercise (aerobic or anaerobic) and chronobiology (morning or afternoon) on the glycemic metabolism of healthy subjects.Methods Healthy subjects participated in aerobic or anaerobic physical exercise sessions, either in the morning or in the afternoon. Blood was drawn from the subjects before, at the end of the exercise and 2 hours after the end of the exercise. Glycemic parameters were analyzed at these time points. A general linear model test was performed after verifying the normal distribution of the raw data (as assessed by the Shapiro-Wilk test) or after a logarithmic/square root transformation, considering aerobic or anaerobic exercise and morning or afternoon exercise as independent variables.Results Twenty-three subjects (14 women and 9 men) were included in the study. The rate of change in glucose levels was significantly higher at the end of anaerobic exercise compared to aerobic exercise (1.19 ± 0.04 vs. 0.98 ± 0.02, respectively), with a more pronounced decrease in insulin and C-peptide levels following aerobic exercise. In addition, the increase of glucose was higher after the exercise in the morning compared with the afternoon (1.14 ± 0.03 vs. 1.03 ± 0.03, respectively).Conclusions The type of exercise and chronobiology influence short-term glucose metabolism.